Exposure to Arsenic Alters the Microbiome of Larval Zebrafish - Dahan, Dylan; Jude, Brooke A.; Lamendella, Regina; Keesing, Felicia; Perron, Gabriel G. (Frontiers in Microbiology, 2018)
Exposure to environmental toxins such as heavy metals can perturb the development and stability of microbial communities associated with human or animal hosts. Widespread arsenic contamination in rivers and riparian habitats therefore presents environmental and health concerns for populations living near sources of contamination. To investigate how arsenic affects host microbiomes, we sequenced and characterized the microbiomes of twenty larval zebrafish exposed to three concentrations of arsenic that are found in contaminated water -- low (10 ppb), medium (50 ppb) and high (100 ppb) for twenty days. We found that even a small concentration of arsenic changed the overall microbial composition structure and diversity of microbial communities, causing dysbiosis in developing larval zebrafish microbiota. In addition, we found that a high concentration of arsenic also increased the abundance of a class 1 integron, an integrase-dependent system facilitating the horizontal transfer of genes conferring resistance to antibiotics and heavy metals.